DESIGN A MOSQUE MANAGEMENT INFORMATION SYSTEM (SIM2) TO FACILITATE THE MANAGEMENT OF REPORTS AND ACTIVITY INFORMATION - Jekri Pefriand; Laga Kamalmalik; Arfhan Prasetyo; Mugi Raharjo (Journal of Information System, Informatics and Computing, 2023)
Industry 4.0 will be utilised by some Muslims who follow the development of information technology. The mosque is one of the places of worship in which there is an organisation. One of the divisions or sections in the mosque's organisational structure that is most rarely found is the IT (Information and Technology) field. One of the tasks of the IT field is to manage the information system in the form of documentation of activities and activities carried out at the mosque. Collecting all information about management in some mosques that follow technological developments such as activity & financial information which is useful as a source of information to determine the first steps in an effort to prosper the mosque. Such is the case at the Al-Ikhlash Karet Tengsin Mosque, Tanah Abang, Central Jakarta. Currently, information on activities conveyed to the community is still in the form of announcements posted on the mosque notice board and the process of processing financial data and information is still not integrated. As a result of this, there are many obstacles faced by the mosque management in its management affairs such as financial management and special activities of the Al-Ikhlash Mosque. The data collection method technique for making the programme is by observing interviews with partners. This interview aims to find out the problems that are being experienced. Completing the programme and obtaining satisfaction surveys from partners and participants who attended the socialisation training. It is known that the overall level of community satisfaction with community service has an average score of 4.61 and is in the Strongly Agree category. Community satisfaction related to the community service programme can be an indicator of the success of the community service programme. In addition, the community also expects cooperation with other parties, so that when the community service programme is completed, the community is able to continue the programme.